Code-Switching as a Multilingual Strategy in Conversations among Indonesian Graduate Dtudents in the US - Pujiastuti, Ani (Journal of English and Education (JEE), 2007)
Choosing what language to use and what cultural values to adopt may be problematic for international students undertaking cross-border studies in the U.S. This –problem occurs simply because the students bring with them the various cultural values and beliefs, and language-related identities with them in a new linguistic environment. This paper aims at identifying the major patterns of language use among Indonesian students in the U.S. and the reasons of Indonesian students in choosing particular languages in conversations.The study involved eighteen Indonesian students undertaking master and doctoral studies in some American universities. The survey and interview methods are used to gather the data. The results of the survey and interview disprove my previous prediction that the inter-or intrapersonal mechanism, such as community or institutional norms, accommodation, politeness, physical condition such as fatigue or laziness, and rationality may determine the speakers' language choices. This study indicated that that Indonesians in the U.S. might be aware of the importance of influences such as, cultural values that may directly or indirectly impact the language preference, and some unpredictable and violable arrangements for language choice, such as exclusion/inclusion of others in addition to the apparent communal perception of English as the accepted institutional and social password in the U.S. Additionally, I learned that the students' multilingual strategy was reflected in. their ability to 'play safe' in using the languages in multilingual interactions, by selecting the most comfortable languages in conversations without neglecting others who were within their earshot.